Secure cluster-based data aggregation in wireless sensor networks with aid of ECC. (24th June 2019) - SriVenkateswaran, C.; Sivakumar, D.
In WSN, to overcome the energy consumption issue, some of the researchers used cluster head-based approach to send the data to the sink node. In this paper, we have presented the approach for cluster head selection for data aggregation in wireless sensor network. For clustering the node, hybrid k means and fuzzy c-means clustering algorithm is used. Then we select the cluster head from each cluster. Every node in the wireless sensor network sends their sensed data to the cluster head. The data aggregation is done in the cluster head. Finally base station is received the data from one cluster head, in order to reduce the transmission time here the proposed method is remove the duplicate data and then secure transmission is done by elliptic curve cryptography (ECC). The performance of the proposed technique is evaluated by overall running time and also the encryption and decryption time.